2011
DOI: 10.1111/j.1475-097x.2011.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and sensitivity of muscle reoxygenation and oxygen uptake recovery kinetics following running exercise in the field

Abstract: The purpose of this study was to assess the reliability of postexercise near-infrared spectroscopy (NIRS)-derived measurements and their sensitivity to different exercise intensities in the field. Seventeen athletes (24·1 ± 5·6 year) repeated, on three occasions, two 2-min submaximal shuttle-runs at 40% and 60% of V(IFT) (final speed of the 30-15 intermittent fitness test) and a 50-m shuttle-run sprint (Sprint), with (OCC) or without (CON) repeated transient arterial occlusions of the medial gastrocnemius duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 37 publications
(94 reference statements)
4
41
1
Order By: Relevance
“…Indeed, moderate and strong intratest ICC values were observed when monitoring HbO 2min and TSI min during most single-repetition sets at each exercise intensity. The easy-to-use non-invasive nature of NIRS, and its practicality during tests in the laboratory or the field, make it an attractive method to monitor muscle oxygenation status during and following exercise (Buchheit et al, 2011). Moreover, the results of the current investigation are similar to those reported for the reliability of NIRS to quantify muscle re-oxygenation and oxygen uptake recovery kinetics following intermittent running activity (Buchheit et al, 2011).…”
Section: Reliability Of Nirs Measuressupporting
confidence: 78%
“…Indeed, moderate and strong intratest ICC values were observed when monitoring HbO 2min and TSI min during most single-repetition sets at each exercise intensity. The easy-to-use non-invasive nature of NIRS, and its practicality during tests in the laboratory or the field, make it an attractive method to monitor muscle oxygenation status during and following exercise (Buchheit et al, 2011). Moreover, the results of the current investigation are similar to those reported for the reliability of NIRS to quantify muscle re-oxygenation and oxygen uptake recovery kinetics following intermittent running activity (Buchheit et al, 2011).…”
Section: Reliability Of Nirs Measuressupporting
confidence: 78%
“…The present study showed similar relative reliability, however, inferior absolute reliability for recovery kinetics of TSI compared to onset kinetics. Problematic fitting of the mono‐exponential function seems a key issue in the reliability of recovery kinetics, as has been confirmed by other authors (Buchheit et al ., ). It is especially troublesome for [HHb] recovery kinetics, where it was not feasible in six tests, with the remaining recovery responses producing lower coefficients of determination than for TSI.…”
Section: Discussionmentioning
confidence: 97%
“…In healthy subjects the technique has shown good reproducibility that is uninfluenced by the type of exercise 54, 58. Good agreement has been demonstrated between NIRS derived recovery time constants and phosphocreatine (PCr) recovery time constants found with magnetic resonance spectroscopy (MRS) 59 as well as good correlation with in vitro assessed oxidative capacity via muscle biopsy analysis 60 …”
Section: Assessment Of Skeletal Muscle Truev˙o2mentioning
confidence: 99%